PRODUKSI DAN EVALUASI KUALITAS SUSU BUBUK ASAL KAMBING PERANAKAN ETTAWA (PE) [Production and Quality Evaluation of Ettawa-Crossbred Goat Milk Powder] - . Widodo; Afina Viyunnur Rachmawati; Rina Chulaila; I Gede Suparta Budisatria (Jurnal Teknologi dan Industri Pangan, 2012)
The objective of this study was to produce milk powder from Ettawa-crossbred goat milk and subsequently evaluate the quality of the products. The raw material used was Ettawa-crossbred goat fresh milk with total solid, lactose, fat, and protein content of 15.93%, 4.2%, 4.8% and 4.7%, respectively. Milk with final total solid of 17.5% and 20% were prepared for spray drying by adding skim milk powder. Drying was carried out using a spray dryer type Lamp having nozzle size of 0.05 mm with an inlet temperature of 90°C and an outlet temperature of 45°C. Parameters observed were chemical, physical and microbiological qualities. The data showed that milk powder produced from Ettawa-crossbred goat milk had water content of 1.5-1.7%. Further analysis showed that the acidity, proteins, lactose, and fat content were 0.90%, 28.4%, 21.7%, and 22.5%, respectively. The physical analysis showed that milk powder produced from Ettawa-crossbred goat milk had a higher wettability score (143 seconds) as compared to that of commercial products (29 seconds), a higher sieve test score (0.6 g vs 0.004 g), but similar index of insolubility (1.4 ml vs.1.6 ml). The microbiological analysis showed that the Total Plate Count (TPC), Enterobacteriaceae (EB) and presumptive coliforms increased during storage either in refrigerator or room temperature. The increase in TPC, EB and coliforms was substantially higher when products were kept at room temperature than in refrigerator. In conclusion, Ettawa-crossbred goat milk powder had a good nutrition quality, but still need improvement for the physicochemical characteristic including wettability and nutritional enrichment for vitamins and minerals by means of fortification.